Graphene-based terahertz sensor - Chong, Bei En (Nanyang Technological University, 2022)
The main objective of this work is to test the sensitivity of a graphene-based Terahertz sensor, to determine whether it can be used to effectively detect various substances. Terahertz technology is a safe technique that does not destroy the analyte, and has gained increasing popularity in the recent years due to its potential to analyse biological molecular, cellular, tissue and organs effectively and safely. One terahertz technique, known as terahertz spectroscopy has been introduced and applied in various fields from agriculture to aerospace. In this project, I work on a terahertz spectroscopy technique known as attenuated total reflectance (ATR) terahertz spectroscopy. These experiments have been conducted using different analytes and substrates to test whether there is an increase in detection sensitivity when a graphene-based sensor is used. As expected, a graphene-based sensor does improve the sensitivity in detection of substances.